Synthetic oligonucleotides as quantitative PCR standards for quantifying microbial genes - Han, Xingguo; Beck, Karin; Bürgmann, Helmut; Frey, Beat; Stierli, Beat; Frossard, Aline (Frontiers in Microbiology, 2023)
Real-time quantitative PCR (qPCR) has been widely used to quantify gene copy numbers in microbial ecology. Despite its simplicity and straightforwardness, establishing qPCR assays is often impeded by the tedious process of producing qPCR standards by cloning the target DNA into plasmids. Here, we designed double-stranded synthetic DNA fragments from consensus sequences as qPCR standards by aligning microbial gene sequences (10 -20 sequences per gene). Efficiency of standards from synthetic DNA was compared with plasmid standards by qPCR assays for different phylogenetic marker and functional genes involved in carbon (C) and nitrogen (N) cycling, tested with DNA extracted from a broad range of soils.Results showed that qPCR standard curves using synthetic DNA performed equally well to those from plasmids for all the genes tested. Furthermore, gene copy numbers from DNA extracted from soils obtained by using synthetic standards or plasmid standards were comparable. Our approach therefore demonstrates that a synthetic DNA fragment as qPCR standard provides comparable sensitivity and reliability to a traditional plasmid standard, while being more time-and cost-efficient.